2014
DOI: 10.1016/j.neurobiolaging.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction and gray matter atrophy in amnestic mild cognitive impairment

Abstract: Recent studies have shown that impairment in executive function (EF) is common in patients with amnestic mild cognitive impairment (aMCI). However, the neuroanatomic basis of executive impairment in patients with aMCI remains unclear. In this study, multiple regression voxel-based morphometry analyses were used to examine the relationship between regional gray matter volumes and EF performance in 50 patients with aMCI and 48 healthy age-matched controls. The core EF components (response inhibition, working mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 51 publications
6
49
0
Order By: Relevance
“…Furthermore, TMT B predicted variation in the middle temporal cortex on trend level, which is in line with previous findings [30]. TMT B relies on both working memory and task switching ability [35], functions subserved by regionally distributed brain regions [37,53,54]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, TMT B predicted variation in the middle temporal cortex on trend level, which is in line with previous findings [30]. TMT B relies on both working memory and task switching ability [35], functions subserved by regionally distributed brain regions [37,53,54]. …”
Section: Discussionsupporting
confidence: 90%
“…While verbal memory has been reliably coupled with MTL integrity [41], executive function measured by TMT B performance has been associated with cortical thickness in frontal, temporal and parietal brain regions [37,53,54]. Since several studies have delineated the utility of RAVLT and TMT B, and these tests are readily available to the clinician [28,29,38,39], we were interested in how they compared to a composite test score as predictors of variance in the 2 neuroimaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Centrally, three research axes are proposed:

Using specific EF tasks: future studies should use tasks evaluating each basic EF components (updating, shifting, and inhibition), e.g., the nine Miyake’s tasks (Miyake et al, 2000; see Figure 1B) which have been found to specifically explore the distinct EF subcomponents. The validity of these tasks has been reinforced by studies confirming the underlying multi-factorial model of EF in various healthy samples (Hedden and Yoon, 2006; Vaughan and Giovanello, 2010; Zheng et al, 2014). Although Miyake’s tasks have not yet been applied to psychiatric population, they are now widely used to explore EF (Fournier-Vicente et al, 2008) and present higher sensitivity and lower ceiling effect than classical EF tasks.

…”
Section: What Should Be Done In Future Studies?mentioning
confidence: 96%
“…The validity of these tasks has been reinforced by studies confirming the underlying multi-factorial model of EF in various healthy samples (Hedden and Yoon, 2006; Vaughan and Giovanello, 2010; Zheng et al, 2014). Although Miyake’s tasks have not yet been applied to psychiatric population, they are now widely used to explore EF (Fournier-Vicente et al, 2008) and present higher sensitivity and lower ceiling effect than classical EF tasks.…”
Section: What Should Be Done In Future Studies?mentioning
confidence: 96%
“…We describe how alterations in the network of white matter connections in the brain relate to differences in executive abilities found in individuals with MCI. Although executive abilities and MCI have previously been linked using DTI [11], the use of network measures to describe this relationship is not well characterised in the literature.…”
Section: Introductionmentioning
confidence: 99%